Elevenlabs Text-To-Speech and Arabic Listening Achievement in Pesantren - Asep Sunarko; Muhamad Solehudin; Nurin Sakinah (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Background: Listening comprehension remains a major challenge in Arabic language learning, particularly in non-Arabic-speaking contexts such as Indonesian pesantren. Limited exposure to authentic auditory input often hinders phoneme recognition, prosodic awareness, and comprehension of connected speech. Recent advances in artificial intelligence, especially Text-to-Speech (TTS) technology, offer new opportunities to provide consistent, high-quality auditory input that can enhance listening skill development. Research Objectives: This study aims to examine the effectiveness of the ElevenLabs Text-to-Speech technology in improving students’ Arabic listening comprehension and to explore students’ perceptions regarding the clarity, authenticity, and motivational impact of AI-generated Arabic audio. Methodology: The study employed a mixed-methods quasi-experimental pre-test–post-test design complemented with interviews and classroom observations. Sixty intermediate students from Pondok Pesantren Darullughah Wadda’wah were assigned to an experimental group and a control group. The experimental group used ElevenLabs TTS materials, while the control group used teacher-narrated audio. Quantitative data were analyzed using paired-sample t-tests and qualitative data were processed through thematic analysis. Results: The findings revealed a significant improvement in the experimental group’s listening scores, increasing from a mean of 63.2 to 82.7, while the control group showed only moderate improvement from 64.5 to 71.4. The statistical analysis indicated a significant difference (p < 0.05). Qualitative results also showed that students perceived the AI-generated voices as clearer, more authentic, and emotionally engaging, which enhanced their motivation and reduced listening anxiety. Unique Contribution: This study contributes to the emerging field of AI-assisted Arabic language education by demonstrating how human-like TTS technology can be effectively integrated into pesantren-based learning environments while maintaining both pedagogical and spiritual values. Conclusion: The study confirms that ElevenLabs TTS significantly enhances Arabic listening comprehension by providing consistent, expressive, and cognitively accessible auditory input for learners. Recommendations: Future studies are recommended to explore long-term applications of AI-based listening tools across other Arabic language skills and in broader Islamic educational contexts.